Optimasi Penjadwalan Jam Kerja Part Time menggunakan Algoritme Genetika (Studi Kasus: Haga Coffee Shop Malang) - Angky Christiawan Rongre; Budi Dharma Setiawan; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Haga coffee shop is a coffee shop that provides various types of drinks using coffee as a basic ingredient besides that there are various kinds of drinks besides coffee such as chocolate and green tea and has three outlets. Haga coffee shop also opens part time for students who want to fill their free time between lectures free time between classes and additional allowance also adds expertise in the work world to make part time according to the choices of many students. This makes the manager of Haga coffee shop required to be able to make part-time work schedules that are not convoluted with the lecture schedules of their employees or students. Scheduling is the activity of finding a path that is in line with expectations in order to create an optimized visit schedule. Genetics algorithms is one method in finding solutions to scheduling problems that are often used by researchers. Genetic algorithms were used for 8 employees of Haga coffee shop with a population of 150, the number of generation 50 and combinaton Cr 0,2 & Mr 0,9 were the besst fitness values.